French fast food and the myth of Americanisation. (2nd April 2020) - Poole, Benjamin
ABSTRACT: The rise of fast food in France has been understood by the media and scholars alike as a prime example of 'Americanisation'. What could better illustrate the threat of American-led industrialisation and globalisation than Big Macs replacing traditional French gastronomy? However, this article argues that this Americanisation narrative is a myth that has obscured French complicity in the transnational development of fast food. French leadership in the industrialisation of the restaurant goes back at least to the turn of the twentieth century with Auguste Escoffier's standardisation of dishes and techniques. In the 1960s and 1970s, Jacques Borel's food-service empire pioneered industrial innovations that came to typify fast food, well before American chains like McDonald's arrived in France. Even the American-styled hamburger chains that proliferated in France in the 1980s were initially mostly European-owned. But branding fast food as American enhanced its exotic appeal while relegating its unsavoury industrial practices to the forces of Americanisation. This in turn nourished a counter-myth of French gastronomic traditionalism and artisanship, that proved highly lucrative. Examining a range of popular media, this article reveals how national myths are constructed (and reconstructed) to serve disparate interests in a global context.